Profiles and factors associated with poor glycemic control among inpatients with diabetes mellitus type 2 as a primary diagnosis in a teaching hospital - Ismail, A.; Suddin, L.; Sulong, S.; Ahmed, Z.; Kamaruddin, N.A.; Sukor, N. (Medknow Publications, 2016)
Context: Diabetes mellitus is a growing health problem in most countries. In Malaysia, there was an increase in prevalence over the years. This makes diabetes also a growing concern in Malaysia, which warrants strengthening of the prevention and control programme. Aims: This paper aims to describe the profiles of diabetes mellitus type 2 in tertiary setting and to identify the risk factors for high level of HbA1c among the study population. The findings will give a glimpse on current status of diabetes in our country and may reflect the achievement of the country in combating this disease. Settings and Design: A cross-sectional study was conducted in UKM Medical Centre. Methods and Material: Medical records of patient with E11 ICD-10 code were collected using Case Report Form. Statistical Analysis Used: Descriptive analysis done of mean and median while test of association were done using Spearman correlation and logistic regression. Results: The results showed that majority of inpatients of DMT2 showed mean age of 58.8 + 12.6 years and most were males (56.7%) with secondary level of education (41.7%). Median duration of disease was 12.0 + 11.0 years with median HbA1c level of 8.9 ± 4.4%. Only small proportion of patients achieved the desired level of HbA1c <6.5% (21.3%) and significant association was found with tertiary level of education [AOR=0.10, 95%CI=0.01-0.96] and with type of anti-diabetic therapy [AOR=15.90, 95%CI=2.03-124.30]. Conclusions: In conclusion, diabetes mellitus type 2 inpatients still showed unsatisfactory glycemic control and holistic approach using health education should be advocated continuously in the future in view of education being one of the predictors for the good HbA1c outcome.